Awards: A Disregarded Source of Motivation - Frey, Bruno S.; Neckermann, Susanne; Justus Liebig University Giessen (My University, 2009)
Awards are prevalent in all societies and at all times. So far, however, they have escaped the attention of economists. This paper presents a first analysis of awards, distinguishing them from purely monetary forms of rewards. Additionally, popular notions about the use and prevalence of awards are addressed with descriptive statistics from the International Who's Who.
Keywords: ddc:100; ddc:330